The Role of Teachers in Implementing the Islamic Religious Education Curriculum Based on Noble Morals - Juliani; Bagas Herawan; Fiqri Farhanul Khair; Muhammad Alif Fiqri (Journal of Contemporary Islamic Primary Education, 2024)
The curriculum is one of the most important components in the education system, so it is a tool to achieve educational goals as well as a guideline for implementing education at all types and levels of education. Teachers, as curriculum implementers, must be able to implement the curriculum in learning activities. With an understanding and mastery of the curriculum, teachers can choose and determine the direction and objectives of learning, methods, techniques, media, and assessment tools that are in accordance with the material taught in the teaching and learning process. The question examined in this study is what teachers need to do to implement a noble and morally based Islamic Religious Education curriculum that is not only understood but can also be applied in everyday life. This research is qualitative research with a descriptive approach using interactive and non-interactive methods. To achieve the goal of an effective learning process, especially in facing the challenges of ever-growing social change, curriculum development is very important not only for the government and managers of Islamic educational institutions, but also for the managers of Islamic educational institutions themselves. This is a very serious problem. The development of Islamic religious curriculum in Islamic educational institutions has a big role. Therefore, it is natural that educators and teachers in the field of Islamic education strive to understand and continue to develop the curriculum.